Case report: Senescence as mechanism of resistance to Pembrolizumab in a Lymphoma patient who failed CD19-Targeted CAR-T cell therapy - De Matteis, Serena; Casadei, Beatrice; Lolli, Ginevra; Dicataldo, Michele; Barbato, Francesco; Dan, Elisa; Paccagnella, Andrea; Sinigaglia, Barbara; Bertuzzi, Clara; Arcari, Annalisa; Zazzeroni, Luca; Bernuzzi, Patrizia; et al. (Frontiers in Immunology, 2022)
Background T cells engineered to target CD19 antigen on neoplastic B cells represent the most striking example of CAR-T cell therapy. The success rate of this therapy is affected by several limitations: target antigen loss, and/or acquisition of a senescent/exhausted phenotype by CAR and non-CAR T cells. Case presentation We report on a patient affected by refractory Diffuse Large B-cell Lymphoma who was resistant to CAR T-cell therapy and to two cycles post CAR-T of pembrolizumab (PBZ) due to the evolution into a B-cell Hodgkin-like lymphoma. Owing to the CD30 expression and the Hodgkin-like phenotype, the patient was ultimately treated with Brentuximab-Vedotin and finally underwent remission. Upon PBZ treatment, 100% of circulating CAR-T+ cells showed a persistent CD8+ senescent/exhausted phenotype, while an increase in the percentage of senescent cells was found in the non-CAR CD8+ T cells compartment. Conclusions PBZ is not able to reinvigorate exhausted CAR+ T cells and to confer durable clinical response. We hypothesize that the phenomenon is due to the senescent phenotype of CAR+ T cells, which did not allow PBZ-induced reactivation and proliferative rescue. The phenomenon, together with the loss of CAR-T target CD19 and the shift of non-CAR CD8+ T cells towards a senescent phenotype likely contributed to set up an immune landscape with poor antitumor capacity.